Theoretical study of a recently synthesized azo dyes useful for OLEDs - Gester, Rodrigo; Torres, Alberto [UNESP]; Bistafa, Carlos; Araujo, Raiane S.; Silva, Tercio Almeida da; Manzoni, Vinicius (Elsevier B.V., 2020)
The development of new materials with higher nonlinear optical (NLO) activity is an important goal in photonics and optoelectronics. In this context, a theoretical and systematic investigation on the NLO con-stants of a set of recently synthesized trans-azo-azomethine dyes is performed using the Density Functional Theory. The results suggest how to enhance the electrical properties through an organized substitution of CN and NO2 chemical groups at specific molecular sites. The analyses of NLO parameters, frontier molecular orbitals, energy gap and chemical hardness indicates that the studied compounds should have promising uses as organic light-emitting diodes. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Azo dyes; Hyperpolarizabilities; NLO; Optoelectronics; Optical materials; Energy gap